THE RELATION BETWEEN WESTERN LEGAL TRADITION AND BIOMEDICAL SCIENCES IN THE CONTEXT OF THE ART. 53 (A) OF THE EUROPEAN PATENT COVENTION - Randakevičiūtė, Jurgita (Teisė, 2016)
This paper analyses how the Western legal tradition should react to the development of biomedical sciences, when the latter present innovation, which frequently is comprehensive only to a narrow circle of specialists. This work presents the view of the Western legal system and biomedical sciences as two interacting traditions and seeks to set the main guidelines for further investigation, in order to understand, how the legal system should react to the progress of biomedical sciences and set the appropriate regulation. The art. 53 (a) of the European Patent Convention serves in this work as the starting point for the analysis of the relationship between these two traditions.